María Isabel Corts Giner, A. Ávila Femández, María Consolación España y Ana María Montero Pedrera (1996/3ª). Historia de la educación. - Bernabé Bartolomé Martínez (Universidad Complutense de Madrid, 1997)
Sin resumen